Evaluation of Phytochemical Composition and Antimicrobial Activity of Sweet Potato (Ipomoea batatas) Leaf - Mbaeyi-Nwaoha, I.E.; Emejulu, V.N. (Pakistan Journal of Nutrition, 2013)
Sweet Potato Leave (SPL) powder and its peptone, ethanol and water extracts were subjected to proximate, phytochemical, anti-nutrient and antimicrobial analysis. The results of proximate analysis revealed the presence of high carbohydrate (43.971±0.019-56.472±0.009%) and crude protein (16.497±0.003-28.163±0.003%). The sweet potato leaves powder and the extracts also contain moisture (3.603±0.004-16.921±0.008%), ash (5.563±0.004-10.414±0.007%), fat (0.208±0.007-14.264±0.002%) and fibre (0.244±0.003-2.764±0.003%), respectively. The phytochemical screening revealed the presence of bioactive compounds in the SPL powder and its extracts namely; tannins, alkaloids, steroids, glycosides, saponins, flavonoids and soluble carbohydrates. The SPL powder had the highest content of these bioactive compounds with alkaloid having the highest value of 3.784±0.007mg/100g, followed by flavonoid (3.357±0.006mg/100g) and steroid had the lowest value (0.393±0.003mg/100g). The extracts had highest content of flavonoid ranging between 2.762±0.008 and 3.355±0.004 mg/100g and least content of steroid ranging between 0.357±0.002 and 0.375±0.003mg/100g. The anti-nutrient analysis indicated the content of very high amount of oxalate ranging between 1.664±0.004 and 6.254±0.004% in the four samples. They contained lower amounts of phytate (3.897±0.003 to 5.933±0.003mg/100g), cyanide (0.353±0.003 to 1.444±0.004mg/100g) and tannin (5.527±0.002 to 9.010±0.002mg/100g). The antimicrobial activity of the peptone, water and ethanol extracts was tested against Escherichia coli, Salmonella typhi, Staphylococcus aureus, Aspergillus niger, Penicillium spp., Pseudomonas aeroginosa and Klebsiella pneumonia. The water extract showed the best antimicrobial activity by inhibiting the growth of all the organisms except E. coli and Penicillium spp at different concentrations of the extract. While the ethanol and peptone extracts only had a minimal activity against Salmonella typhi.